A rare sacral localization of giant cell tumor in a young adult female: a case report - Tupputi, Umberto; Eusebi, Laura; Stronati, Andrea; Carpagnano, Francesca Anna; Testini, Valentina; Bartelli, Francesco; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
We reported the case of a 42-years-old woman who suffered from a giant cell tumor of sacrum. Although the giant cell tumor primarily affects the long bones, especially those of the knee joint, it can rarely affect the axial skeleton and the sacrum. The onset of symptoms is generally insidious and may include locoregional pain and swelling as well as movement deficits if nerve roots are involved at this level. In this case report we discuss on the radiographic imaging, computed tomography and magnetic resonance imaging features of this type of tumor in an unusual location of the disease.